Hypermobile Disorders and Their Effects on the Hip Joint - Clapp, Ian M.; Paul, Katlynn M.; Beck, Edward C.; Nho, Shane J. (Frontiers in Surgery, 2021)
Hypermobility, or joint hyperlaxity, can result from inherited connective tissue disorders or from micro- or macro-trauma to a joint. The supraphysiologic motion of the hip joint results in capsuloligamentous damage, and these patients have a propensity to develop femoroacetabular impingement syndrome (FAIS) and labral injury. In this review the recent literature evaluating the definitions, history, incidence, genetics, and histology of hypermobile disorders are investigated. We then review the clinical evaluation, natural history, and resulting instability for patients presenting with a hypermobile hip. Lastly, treatment options and outcomes will be highlighted.